Peningkatan Kemampuan Menulis Siswa melalui Pembuatan Infografik Pokok Bahasan Teks Prosedur - Desy Ratna Intani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This research is entitled "Improving Students' Writing Ability through Making Infographics on the Main Topics of Procedure Texts". The subjects of this research were students in class VII A at SMP Muhammadiyah 3 Karangpandan for the 2022/2023 academic year. The aims of this research are: (1) To determine the condition of writing ability of class VII A students of SMP Muhammadiyah 3 Karangpandan before learning using infographics is carried out, (2) To find out how making infographics on the subject of procedural texts can improve students' writing skills, and (3) To find out the results of improving the writing skills of class VII A students of SMP Muhammadiyah 3 Karangpandan after learning was carried out through making infographics on the subject of procedural texts. Based on the aspects to be achieved, the Classroom Action Research (CAR) method was used in this research because in general PTK is very suitable for improving the quality of research subjects. Based on the research results, it was found that making infographics in procedural text material can improve students' reading skills in learning.